Composting and kinetic dynamic modelling of oil palm empty fruit bunch with periodic addition of anaerobic sludge - Hasan, Muhamad Yusuf (2020)
The objectives of this study were first to evaluate the efficiency of the current mathematical model in composting for its environmental correction function and to suggest correction functions. Second, to develop in-vessel type periodic addition composting with lignocellulosic degradation and dominant microbes through DNA quantification, and finally to propose a new mathematical model with a different initial C / N ratio including related parameter estimation. In this work, the existing mathematical model form is evaluated in terms of flexibility in the use of a model that should be derived from measurable data. The initial C / N ratio and the periodic addition of sludge were investigated in a number of OM composition analyses. Composting was performed in a vessel style composter. The presence of microbes was detected using quantitative PCR, which tests the amount of DNA. A comparative experiment was also performed for the periodic addition of sludge and pure water, and no addition was investigated. Subsequently, the three initial C / N ratios for periodic addition of sludge composting, C / N (27:1), C / N (37:1), C / N (47:1) with OPEFB ratio and sludge were 1:4, 1:1 and 4:1. The OM composition analysis was conducted using an acid digestion fibre analysis. Solvita ® compost maturation package has been used for compost maturation.The results showed that the growth of the bacteria peaks during the thermophilic process with the highest DNA copy number and the highest degradation rate at 2.07% OM per day and only the addition of water capable of reaching 0.6% OM per day. Indeed, C / N (37:1) with a ratio of 1:1 OPEFB and sludge was able to reduce the OM loss to 74.51% at the maturity stage of the Solvita ® compost maturity package. This indicates that it was not appropriate to add unnecessary sludge. The best overall degrader properties were achieved with the initial C / N(37:1) provided by the periodic addition of the sludge leading to the proposed C / N correction coefficient in the mathematical mass and energy balance model as follows: